The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10198-009-0146-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived job security and sickness absence: a study on moral hazard

Abstract: A moral hazard problem was investigated by analysing the individual behaviour of female and male employees with regard to utilisation of sickness insurance in connection with perceived job security. It was hypothesised that employees with a higher perceived job security take more frequent sickness absence. Perceived higher job security is indicated by three variables, namely a permanent job contract, no unemployment history, and native ethnicity. The effect of perceived job security is expected to be stronger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…One reason for this might be the strong legal protection towards unreasonable dismissal (which dismissal due to sick leave is considered to be) and the strong positions of the unions. However, this result was not unexpected based on prior studies showing that the effect of unemployment on sickness absence mainly targets short-term absence (Khan and Rehnberg, 2009). In addition, women's long-term absence has been shown in a Swedish study not to be affected by unemployment rates (Knutsson and Goine, 1998).…”
Section: Simulation Of Productivity Gains In Terms Of Reduced Sickmentioning
confidence: 77%
See 1 more Smart Citation
“…One reason for this might be the strong legal protection towards unreasonable dismissal (which dismissal due to sick leave is considered to be) and the strong positions of the unions. However, this result was not unexpected based on prior studies showing that the effect of unemployment on sickness absence mainly targets short-term absence (Khan and Rehnberg, 2009). In addition, women's long-term absence has been shown in a Swedish study not to be affected by unemployment rates (Knutsson and Goine, 1998).…”
Section: Simulation Of Productivity Gains In Terms Of Reduced Sickmentioning
confidence: 77%
“…It has indeed been shown that perceived job security affects sickness absence in Sweden, although this mostly affects short-term absence. Interestingly, there is only a weak effect on long-term absence (measured as longer than 7 days) (Khan and Rehnberg, 2009 (2007) shown that a change in the Swedish labour legislation in 2001 that reduced the job security of employees affected short-term much stronger than long-term absence. This is also connected to the issue of moral hazard which is expected to be more related to short-term than long-term absence as a medical certificate is required after the first 7 days.…”
Section: Instrumentsmentioning
confidence: 99%
“…Of the 30−34 and 35−54 year olds, 63−70% and 74−85%, respectively, had permanent contracts. According to the results of a Swedish study, women with nonpermanent contracts had significantly lower numbers of short and long SAs than permanent employees, but permanence did not affect SAs among men 26) . We were unable to investigate the effect of job permanence on SAs because of the small numbers of permanent employees in the younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity might be related to the fact that long‐term sickness absence differs from overall sickness absence. In short, compared with short‐term sick leave, long‐term sickness absence is likely to be more closely connected with illness and disease (Khan & Rehnberg, 2009; Kivimäki et al., 2003), and is therefore less likely to be more extensively affected by changes in regulations concerning aspects such as compensation levels and marginal adjustments to eligibility rules.…”
Section: Discussionmentioning
confidence: 99%